2019
DOI: 10.18502/sjms.v14i3.5210
|View full text |Cite
|
Sign up to set email alerts
|

Hemogram abnormalities in apparently healthy first-time blood donors in Libreville, Gabon.

Abstract: Background: The objective of this study was to determine complete blood count (CBC) abnormalities in Libreville blood donors to advocate for hemoglobin pre-donation implementation and to take into account CBC results in blood donation qualification. Methods: This retrospective study was conducted with 4573 blood donors in March 2016 and from January to April 2017. CBC was performed using SysmexXP-300TM hematology analyzer (SYSMEX Corporation, Kobe, Japan). Results: Blood donors were predominantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“… 5 Anemia has a significant impact in Gabon, with prevalence rates of 69.5% in children and 56.7% in adolescents reported, with rates reaching 60.6% in women. 6 , 7 , 8 While Libreville has reported 69.4% and 45% anemia prevalence rates, respectively, among female and male first-time blood donors, 9 data for Lambaréné remains limited. Simultaneously, a study found that the prevalence rate of Loa was 26.4%, Mansonella perstans was 14.6%, and coinfections were 5.3% in the general Gabonese population.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Anemia has a significant impact in Gabon, with prevalence rates of 69.5% in children and 56.7% in adolescents reported, with rates reaching 60.6% in women. 6 , 7 , 8 While Libreville has reported 69.4% and 45% anemia prevalence rates, respectively, among female and male first-time blood donors, 9 data for Lambaréné remains limited. Simultaneously, a study found that the prevalence rate of Loa was 26.4%, Mansonella perstans was 14.6%, and coinfections were 5.3% in the general Gabonese population.…”
Section: Introductionmentioning
confidence: 99%